Inflation Targeting : Theory and Policy Implications - Green, J. (IMF Working Papers; Working Paper ;, 1996)
As with many monetary policy frameworks, inflation targeting is subject to the well-known problem of inflation bias. With inflation targeting, however, the bias becomes apparent not as inflation above desired levels, but as a wedge between the announced target and observed inflation. This inconsistency could render the framework neither credible nor enforceable since the target is overshot on average. The problem can be addressed by assigning price stability as the single policy objective or by assigning a joint target for both inflation and output, provided that they are consistent. Many inflation targeting countries take the joint target approach implicitly through transparency measures which publicly assess monetary conditions in terms of potential output and output gaps.